2016
DOI: 10.1002/lary.26171
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multi‐institutional transnasal esophagoscopy: Predictors of a change in management

Abstract: 2b. Laryngoscope, 126:2667-2671, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…In patients with a history of HNCA presenting with dysphagia, transnasal esophagoscopy (TNE) is a validated tool for evaluation and diagnosis of esophageal pathology . Office‐based TNE is a safe, effective, and well‐tolerated procedure that can be performed using only topical anesthesia .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In patients with a history of HNCA presenting with dysphagia, transnasal esophagoscopy (TNE) is a validated tool for evaluation and diagnosis of esophageal pathology . Office‐based TNE is a safe, effective, and well‐tolerated procedure that can be performed using only topical anesthesia .…”
Section: Introductionmentioning
confidence: 99%
“…3 In patients with a history of HNCA presenting with dysphagia, transnasal esophagoscopy (TNE) is a validated tool for evaluation and diagnosis of esophageal pathology. [4][5][6] Office-based TNE is a safe, effective, and well-tolerated procedure that can be performed using only topical anesthesia. 4,5,7 A multi-institutional prospective TNE study found that in patients with a history of HNCA with dysphagia, TNE led to a change in management.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in the diagnostic workup of hypopharyngeal carcinoma, inspection of the proximal esophagus is usually performed under general anesthesia to determine the distal border of the tumor. With the introduction of TNE, examination of the esophagus for these indications can be performed in the outpatient clinic under topical anesthesia and additional indications are likely to be developed and established in the future [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%